Drosophila mutants suggest a strong drive toward complexity in evolution. Issue 1 (20th January 2013) - Fleming, Leonore; McShea, Daniel W.
SUMMARY The view that complexity increases in evolution is uncontroversial, yet little is known about the possible causes of such a trend. One hypothesis, the Zero Force Evolutionary Law (ZFEL), predicts a strong drive toward complexity, although such a tendency can be overwhelmed by selection and constraints. In the absence of strong opposition, heritable variation accumulates and complexity increases. In order to investigate this claim, we evaluate the gross morphological complexity of laboratory mutants in Drosophila melanogaster, which represent organisms that arise in a context where selective forces are greatly reduced. Complexity was measured with respect to part types, shape, and color over two independent focal levels. Compared to the wild type, we find that D. melanogaster mutants are significantly more complex. When the parts of mutants are categorized by degree of constraint, we find that weakly constrained parts are significantly more complex than more constrained parts. These results support the ZFEL hypothesis. They also represent a first step in establishing the domain of application of the ZFEL and show one way in which a larger empirical investigation of the principle might proceed.